2019
DOI: 10.1108/s1057-629020190000019008
|View full text |Cite
|
Sign up to set email alerts
|

The Immigrant Health Differential in the Context of Racial and Ethnic Disparities: The Case of Diabetes

Abstract: Purpose: Social and economic disparities between racial/ethnic groups are a feature of the American context into which immigrants are incorporated, and a key determinant of population health. We ask whether racial/ethnic disparities in diabetes vary by nativity and whether native-immigrant disparities in diabetes vary by race and over time in the United States. Methods: Using the 2000–2015 National Health Interview Survey, we estimate logistic regressions to examine the interaction of race/ethnicity, nativit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 73 publications
(99 reference statements)
2
11
0
Order By: Relevance
“…While all U.S.-born participants reported higher uptake rates than foreign-born participants, there was no foreign-born disadvantage observed among non-Hispanic Blacks. This is similar to previous studies that commonly found a foreign-born advantage for Black adults in terms of the prevalence of diabetes [ 21 ] and disability [ 22 ]. Their higher level of English proficiency than other foreign-born racial/ethnic groups [ 23 ] and higher educational attainment levels and household income than U.S.-born Blacks [ 23 ] might have contributed to the foreign-born advantage in relation to flu vaccination among Blacks.…”
Section: Discussionsupporting
confidence: 91%
“…While all U.S.-born participants reported higher uptake rates than foreign-born participants, there was no foreign-born disadvantage observed among non-Hispanic Blacks. This is similar to previous studies that commonly found a foreign-born advantage for Black adults in terms of the prevalence of diabetes [ 21 ] and disability [ 22 ]. Their higher level of English proficiency than other foreign-born racial/ethnic groups [ 23 ] and higher educational attainment levels and household income than U.S.-born Blacks [ 23 ] might have contributed to the foreign-born advantage in relation to flu vaccination among Blacks.…”
Section: Discussionsupporting
confidence: 91%
“…Reflecting the disproportionate impacts of T2D among the overall US Latinx population discussed above, Latinx immigrants are also at disproportionate risk, and T2D has been rated as the most significant health-related threat for Latinx immigrants [12]. While some Latinx immigrants arrive with better health than their USA-based counterparts, the advantage decreases in relation to the amount of time they live in the USA [13]. One study of healthcare utilization among Latinx immigrants with T2D found that undocumented immigrants experienced notably poorer T2D outcomes than immigrants with documentation [14].…”
Section: Diabetes Health Disparities Among Latinx Immigrantsmentioning
confidence: 99%
“…In New Mexico, the second poorest state [46], nearly 50% of the population is Latinx (49.3%) [47], and Latinx poverty is 21.3%. 12 There are approximately 60,000 undocumented Latinx immigrants in New Mexico, 13 and immigrants are known to experience poverty at an even higher rate. Given that individuals in New Mexico living in poverty are three times more likely to have diabetes than those making over $50,000 a year [48], the diabetes risk for low-income, undocumented Latinx immigrants is disproportionately high and is recognized as a significant health threat in the immigrant community.…”
Section: A Case Study From New Mexicomentioning
confidence: 99%
See 1 more Smart Citation
“…as diabetes and heart disease, also vary by REN and can have a substantial impact on the risk of developing FL [44][45][46][47].…”
Section: Plos Onementioning
confidence: 99%